SODIUM-GLUCOSE CO-TRANSPORTER 2 INHIBITOR (SGLT2i)-INDUCED HYPERCALCEMIC ENCEPHALOPATHY IN AN ELDERLY PATIENT: A CAUTIONARY TALE IN GERIATRIC PATIENTS - Thewjitcharoen, Yotsapon; Vongterapak, Somboon; Butadej, Siriwan; Nakasatien, Soontaree; Krittiyawong, Sirinate; Kaojaroen, Sming; Himathongkam, Thep; Chatapat, Lapakorn (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION SGLT2i is currently being advocated as preferred medication in high-risk patients with diabetes. However, elderly patients are prone to known and less-known side effects from this medication. Moreover, polypharmacy can contribute to higher incidence of adverse effects from SGLT2i. CASE An 80-year-old Thai woman with uncontrolled type 2 DM, hypertension and CKD stage 3 (baseline GFR 32 mL/ min/1.73 m2 ) treated with insulin, linagliptin, dapagliflozin and hydrochlorthiazide presented with altered mental status. Dapagliflozin was prescribed 4 months earlier to control her diabetes (A1C 8.1%). Laboratory work-up at initial admission showed acute kidney injury (GFR 21 mL/ min/1.73 m2 ) and severe hypercalcemia of 13.3 mg/dL. Further investigations included low levels of PTH of 7 pg/ ml (reference range 15-65), normal 25-hydroxy vitamin D of 31 ng/ml (reference range 30-100), and a normal level of TSH of 2.3 mU/ml (reference range 0.3-4.2). saline hydration led to improvement in hypercalcemia, renal function, and mental status over 48 hours. She is currently stable at 12 months after discharge. CONCLUSION SGLT2i is a unique and promising anti-diabetic agent. However, post-marketing surveillance data revealed various unexpected adverse events from this medication. Although the exact mechanisms are unclear, SGLT2i may predispose patients to hypercalcemia from various mechanisms including dehydration from osmotic diuresis, increased intestinal calcium absorption due to inhibition of SGLT1, and impact of concomitant medications especially diuretics. Clinicians must take greater care when prescribing SGLT2i to elderly patients.